Optimisation of the production of a selenium-enriched polysaccharide from Cordyceps cicadae S1 and its structure and antioxidant activity - Zhuansun, Wanwan; Xu, Jun; Liu, Hengzhao; Zhao, Ying; Chen, Lulu; Shan, Shufang; Song, Shiqin; Zhang, Haoyu; Dong, Tingting; Zeng, Huawei; Xu, Qinxiang (Frontiers in Nutrition, 2022)
The fermentation medium of a newly identified Cordyceps cicadae S1 was optimised by response surface methodology, with the optimal medium containing sucrose (80 g / L), yeast powder (60 g / L), KH2PO4 (5 g / L), MgSO4·7H2O (1 g / L) and Na2SeO3 (0.1 g / L). Under these conditions, the extracellular polysaccharide yield was 8.09 g / L. A novel selenium-enriched polysaccharide (PACI-1) was isolated from Cordyceps cicadae, purified and identified as a homofructose polysaccharide with a low average molecular weight of 9.95 × 103 Da. The fine structure of PACI-1 was analysed using NMR, CD, and AFM. Additionally, the in vitro antioxidant results showed that the PACI-1 had stronger antioxidant capacity than natural polysaccharides. These results provided a candidate strain for producing selenium polysaccharide and a new polysaccharide from C. cicadae, which showed good antioxidant activity.